Comparative Approach as a Way of Making Historiography More Scientific? - Horský, Jan (Dějiny – teorie – kritika, 2018)
When implemented as part of an ‘analytic approach’, comparative methods can help make historiography more scientific. They can counterbalance the current emphasis on narrativity of historiography. Miroslav Hroch’s studies make valuable contribution to this subject. One should, however, carefully consider a number of questions: Are the analogies we ‘found’ by comparing various processes and situations really ontic in their nature or are they rather just concepts in the sense of ideal types we ourselves project onto the realities studied? Or are they perhaps just plots we use as instruments to help us select phenomena to follow? It also remains to be seen whether some processes of sociocultural change happen analogically because they share the same autonomous internal dynamics or because their actors intentionally and consciously imitate one another. Hroch uses a comparative approach also to consider possibilities and alternatives of development. Alternatives are the subject of ‘contrafactual analysis’, which is an approach to which Hroch is rather sceptical. I do not share his scepticism, at least not in full.